KEBERSIHAN DALAM KONSEPSI ISLAM DAN KRISTEN - Kamaluddin Kamaluddin; Uqbatul Khoir Rambe; Rizky Annisa Fitri (UIN Sumatera Utara Medan, 2021)
Cleanliness is very important for every human being. Cleanliness is one of the main efforts in maintaining human existence. Religion gives very high attention to cleanliness, both physically and mentally. This research is a literature research